การพัฒนาทักษะการพูดภาษาอังกฤษเพื่อการสื่อสารในชีวิตประจำวัน โดยการจัดการเรียนรู้เชิงรุก สำหรับชั้นมัธยมศึกษาปีที่ 1 - ศักดิ์อุดมกุล, รพีพร; วรบุตร, ถาวร; กรมน้อย, อานันท์; ไทยมิตร, แสงอาทิตย์ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 3 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 3 : กันยายน - ธันวาคม 2567, 2024)
This study aimed to: (1) develop English speaking skills for daily communication through Active Learning approaches for Mathayomsuksa 1 students, targeting an 80% passing criteria, with 80% of students meeting the proficiency criteria; and (2) assess students' satisfaction with their English-speaking skill development for daily communication using Active Learning approaches. The target group for this research consisted of 35 Matthayomsuksa 1 students at Ban Phai Phitthayakhom School. The action research instruments were (1) instructional tools, including 3 Active Learning lesson plans spanning a total of 9 hours, and (2) tools for reflective analysis, comprising a teacher’s teaching log, a student behavior observation form, and a speaking skills test for communication across three cycles. Quantitative data were analyzed using mean (µ), standard deviation (σ), and percentage (%), while qualitative data were analyzed through content analysis. The results were found that 1) students achieved an average score of 24.08, equivalent to 80.28% of the full score, with 29 students, or 82.85% of the total, meeting the proficiency criteria, which is higher than the defined criteria. 2) students showed a high level of satisfaction with the development of their English-speaking skills for daily communication through the Active Learning approaches, with an average satisfaction score of 4.56, indicating the highest level of satisfaction.